(untitled) (Analysis in Theory and Applications, 2011)
In this paper, we consider a class of Banach space valued singular integrals. The L^p boundedness of these operators has already been obtained. We shall discuss their boundedness from BMO to BMO. As applications, we get BMO boundedness for the classic g-function and the Marcinkiewicz integral. Some known results are improved.